Water-chemical mode calculation of npp block multistage circulating cooling systems - Кишневский, Виктор Афанасьевич; Чиченин, Вадим Валентинович; Савич, Святослав Лаврентьевич (Technology audit and production reserves, 2014)
Method and algorithm for calculating the number of waterchemical modes of complex circulating cooling systems of TPP and NPP are proposed in the paper. Method for calculating the carbon dioxide balance, allowing to obtain the calculated values of pH and alkalinity forms in circulating water for the studied systems, almost no different from the analytically measured values is improved. Based on the system laboratory and industrial researches for various water classes, the dependence of the deposition rate on the calcium ion concentration in the circulating water is obtained. The necessity of development testing of the studied waterchemical modes of complex circulating cooling systems, which can be made on a scale model of the investigated system with the corresponding thermohydraulic characteristics for the specific water composition is shown. Based on the obtained experimental equation, it is possible to evaluate specific hypothetical values of the mass and thickness of deposits on heat-transfer surfaces of condensers and use this data to predict the operation of existing and newly designed cooling systems of large power facilities.